Elastic cavitation and fracture via injection. Issue 9 (3rd February 2016) - Hutchens, Shelby B.; Fakhouri, Sami; Crosby, Alfred J.
Abstract : We model elasticity and fracture mechanisms giving rise to a critical pressure during soft material property characterization using cavitation rheology. Abstract : The cavitation rheology technique extracts soft materials mechanical properties through pressure-monitored fluid injection. Properties are calculated from the system's response at a critical pressure that is governed by either elasticity or fracture (or both); however previous elementary analysis has not been capable of accurately determining which mechanism is dominant. We combine analyses of both mechanisms in order to determine how the full system thermodynamics, including far-field compliance, dictate whether a bubble in an elastomeric solid will grow through either reversible or irreversible deformations. Applying these analyses to experimental data, we demonstrate the sensitivity of cavitation rheology to microstructural variation via a co-dependence between modulus and fracture energy.